Peran Tenaga Administrasi dalam Meningkatkan Mutu Layanan Administrasi di Sekolah Menengah Atas Datuk Batu Hampar - Nur Anggaini Sinaga; Afriza Afriza (Baitul Hikmah: Jurnal Ilmiah Keislaman, 2025)
Abstract This study aims to reveal the role of school administrative staff in improving the quality of administrative services at Senior hight shcool Datuk Batu Hampar. The research informants consisted of the principal, the head of administration, the vice principal for curriculum affairs, teachers, and students. The study employed a descriptive qualitative approach using observation, interviews, and documentation techniques. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing.The findings indicate that: (1) the role of administrative staff in enhancing the quality of administrative services has not yet functioned optimally; (2) several challenges encountered include delays in the submission of documents by students and parents, late delivery of SKHUN from the students’ previous schools, as well as incomplete teacher files, which hinder proper archiving. In addition, service users expressed dissatisfaction with the available facilities. This situation is influenced by the limited number of administrative staff at the school.